Mimesis and fantasy in Cuentos del reino secreto of José María Merino " (XXI Century. Spanish Literature and Culture, 2007)
The supernatural literature has been, especially in the last years, object ofinterest for readers as well as for critics and theorists. Although the omnipresence ofthe realism, the supernatural literature in Spain has been always cultivated and hasexperimented a splendid renaissance due, in many cases, to writers of the 68generation, which José María Merino belongs to. This article presents an analysis,from the fantastic point of view, of the short stories the book Cuentos del reinosecreto contains and focuses on the study of the settings, the characters, the typologyof fantastic themes and how two opposed concepts such as mimesis and fantasyinteract and are related to each other. Since the author achieves a perfect unionbetween both concepts, I permitted myself to use the term “realismo fantástico” inorder to name this type of short stories.
Keywords: supernatural literature; mimesis; Merino; fantasy; realismo fantástico